Squatting and Urban Commons: Creating Alternatives to Neoliberalism - Martínez, Miguel A.; Polanska, Dominika V. (PARTECIPAZIONE E CONFLITTO, 2020)
Here we introduce the special issue of Partecipazione e Conflitto concerning the theme "Squatting and Urban Commons: Creating Alternatives to Neoliberalism". In particular, we present the context and origins of this edition, the rationale behind these theoretical and empirical concerns, and the main contents of the gathered articles.